PROTECTION OF CIVILIANS AND COUNTER-TERRORISM AS HUMAN SECURITY DIALOGUE OF THE 21ST CENTURY - Kabosha, Francis M. (Journal of Public Policy and Administration, 2020)
Purpose: If human security as defined in the United Nations Development report of 1994, entails shifting the focus from the state security and its interests to the broadest sense of the security of ordinary people and their interests, then the sanctioning of Protection of Civilians (PoC) mandate in peacekeeping missions in 1999, and the counter-terrorism efforts beginning 2005, through to the creation of the United Nations Office of Counter-Terrorism in June 2017 by the General Assembly Resolution 71/291, this article purports that these expansions have deepened and widened the meaning of human security. Methodology: The discussion of the three interdependent concepts has heavily relied on secondary data, to demonstrate that there has been an expanded interpretation of both PoC and counter-terrorism in policy and implementation. Findings: This article argues that, with the shift from state security to individual security, and from traditional military approach to transformative anti-terrorism strategies, human security narrative has enormously expanded to include every aspect of human fears, needs and priorities. Unique contribution to theory, practice and policy: For the union to be effective, it is recommended that all the three concepts should be grounded in human rights approaches, supported by organizational and inter-institution coherence and coordination.